Saving Life Reflected In Lauren Kate's Torment Novel (2010) :An Individual Psychological Approach - Lestariningrum, Wahyu; , Dr. Phil. Dewi Candraningrum, S. Pd, M. Ed; , Siti Fatimah, S,Pd. M. Hum (2013)
This research paper is aimed to show the saving life reflected in Lauren Kate's Torment novel by using an individual psychological approach. Therefore, this study is done by establishing two objectives: the first is to analyze the novel based on the structural elements and the second is to analyze the saving life on the novel based on the individual psychological approach. This research is qualitative research. Primary and secondary data source are types of data of the study. The primary data source is the Torment by Lauren Kate published on 28 September 2010. While the secondary data sources are other materials taken from books, journals, commentaries and internet related to the topic in the research paper. The result on this study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, setting, plot, point of view, and themeare related to each other and form the unity into good quality of novel. Secondly, the individual psychological analysis shows that the effort for saving life of DanielGrigory comes from his fictional finalism and is supported by his inferiority feeling. It makes him strive to reach the superiority and power in emerging the struggle for life to save his girl-friend. In the end, it can be concluded that effort for saving life can be achieved. Finally, Lucinda Price can be saved by Daniel Grigory after the truce over.